PROSPECTS FOR THE DEVELOPMENT OF AN INNOVATIVE ECONOMY IN THE AGRARIAN SPHERE - Shafkarov, Fakhriddin Khudayberdievich (Educational Research in Universal Sciences, 2022)
In this article, the policy of innovation in the agricultural sector is an important direction of the development of the economy of our country. Innovation is a process of economic development associated with the creation of an economic environment based on high technologies. As a result of the introduction of scientific developments in the agricultural sector, the effective use of innovations, the development of non-traditional methods of innovation, and the creation of an innovation environment as the first factor in solving economic problems, an innovative money flow to the country occurs. Investing capital to increase the intellectual potential in agriculture is the main factor for the future development of the agrarian economy. It allows to develop innovative activity in this field, to expand the scope of scientific research, to increase the quality and scientific-practical significance of the introduction of innovative projects. Innovative development in the fields is the development of society, development of society, innovative economic process.